Establishing core outcome sets for gastrointestinal recovery in studies of postoperative ileus and small bowel obstruction: protocol for a nested methodological study. (30th November 2019) - Chapman, S. J.; Lee, M. J.; Blackwell, S.; Arnott, R.; ten Broek, R. P. G.; Delaney, C. P.; Dudi‐Venkata, N. N.; Hind, D.; Jayne, D. G.; Mellor, K.; Mishra, A.; O'Grady, G.; et al.
Abstract: Introduction: Gastrointestinal recovery describes the restoration of normal bowel function in patients with bowel disease. This may be prolonged in two common clinical settings: postoperative ileus and small bowel obstruction. Improving gastrointestinal recovery is a research priority but researchers are limited by variation in outcome reporting across clinical studies. This protocol describes the development of core outcome sets for gastrointestinal recovery in the contexts of postoperative ileus and small bowel obstruction. Method: An international Steering Group consisting of patient and clinician representatives has been established. As overlap between clinical contexts is anticipated, both outcome sets will be co‐developed and may be combined to form a common output with disease‐specific domains. The development process will comprise three phases, including definition of outcomes relevant to postoperative ileus and small bowel obstruction from systematic literature reviews and nominal‐group stakeholder discussions; online‐facilitated Delphi surveys via international networks; and a consensus meeting to ratify the final output. A nested study will explore if the development of overlapping outcome sets can be rationalized. Dissemination and implementation: The final output will be registered with the Core Outcome Measures in Effectiveness Trials initiative. A multi‐faceted, quality improvement campaign for the reporting of gastrointestinal recovery in clinical studies will be launched, targeting international professional and patient groups, charitable organizations and editorial committees. Success will be explored via an updated systematic review of outcomes 5 years after registration of the core outcome set.